2019
DOI: 10.1128/aac.01204-18
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing for Predicting Clarithromycin Resistance in Mycobacterium abscessus

Abstract: Mycobacterium abscessus is emerging as an important pathogen in chronic lung diseases, with concern regarding patient-to-patient transmission. The recent introduction of routine whole-genome sequencing (WGS) as a replacement for existing reference techniques in England provides an opportunity to characterize the genetic determinants of resistance. We conducted a systematic review to catalogue all known resistance-determining mutations. This knowledge was used to construct a predictive algorithm based on mutati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
1
41
1
2
Order By: Relevance
“…On the other hand, three M. massiliense isolates (MAS04: >16μg/ml, MAS06: >16μg/ml, MAS10: >16μg/ml) exhibited inducible resistance to CLR and AZM on the 14 th day. This is contrast with previous studies (Kim et al , 2015; Koh et al , 2010) which demonstrated that inducible resistance to CLR was only present in M. abscessus and not in M. massiliense. Nevertheless, our results support the findings of Li et al .…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other hand, three M. massiliense isolates (MAS04: >16μg/ml, MAS06: >16μg/ml, MAS10: >16μg/ml) exhibited inducible resistance to CLR and AZM on the 14 th day. This is contrast with previous studies (Kim et al , 2015; Koh et al , 2010) which demonstrated that inducible resistance to CLR was only present in M. abscessus and not in M. massiliense. Nevertheless, our results support the findings of Li et al .…”
Section: Resultscontrasting
confidence: 99%
“…Susceptibility rates of M. abscessus complex isolates in the present study showed that MXF has better in vitro activity against M. abscessus (81.8% susceptible) and M. massiliense (60% susceptible) compared to CIP against M. abscessus (9.1% susceptible) and M. massiliense (20% susceptible). This is consistent with other studies showing that MXF has better in vitro activity against M. abscessus and M. massiliense compared to CIP (Kim et al , 2015; Lee et al , 2014; Koh et al , 2010). On the other hand, DOX was found to be more potent against M. abscessus (72.7% susceptible) isolates compared to its activity against M. massiliense (10% susceptible).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…I n our recent study of 203 sequential isolates evaluating the ability of whole-genome sequencing (WGS) to predict clarithromycin resistance in Mycobacterium abscessus (1), we demonstrated high sensitivity but poor specificity of mutations identified in a literature search. Most of the discrepancies occurred in isolates predicted to be inducibly resistant (they showed early time point susceptibility but became resistant after prolonged incubation).…”
mentioning
confidence: 97%